Correction to: Anonymous shell companies: A global audit study and field experiment in 176 countries - Allred, Brent B; Findley, Michael G; Nielson, Daniel; Sharman, J C (Journal of International Business Studies, 2018)
Owing to a production error, a number of values were omitted in Table 1 of this article. A corrected version of this table is provided here. The corrected values are italicized.